Posttraumatic Stress Disorder, Personal Identity, and Meaning in Life in U.S. Veterans. Issue 2 (3rd April 2023) - Davies, Rachel L.; Cox, Sean; Kelley, Michelle L.; Meca, Alan; Milam, Alicia L.; Chae, John W.
ABSTRACT: We examined whether higher levels of posttraumatic stress disorder (PTSD) symptoms and gender were associated with three dimensions of identity (i.e., commitment, in-depth exploration, and reconsideration) and meaning in life (i.e., meaning in life and search for meaning) among recent-era veterans. Participants were 174 post-9/11 veterans (55.8% men; mean age = 36.4 years; SD = 10.1 years) who had experienced one or more deployments. After controlling for combat exposure, age, and time since military separation, more PTSD symptoms were associated with lower presence of meaning in life, lower commitment, lower in-depth exploration, and higher reconsideration. The PTSD symptoms by gender interaction, the association between PSTD symptoms and search for meaning, and direct effects of gender were not significant. These findings suggest the importance of developing a comprehensive conceptualization, which includes identity and meaning in life, for recent-era veterans with PTSD symptoms.